PERAN GOOD CORPORATE GOVERNANCE DALAM MENGURANGI DAMPAK RISIKO PEMBIAYAAN TERHADAP PROFITABILITAS PERBANKAN SYARIAH: (Studi Kasus Bank Umum Syariah Periode 2012-2017) - Hasbi Nurhidayat; Icih Icih; Indah Umiyati (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2019)
The purpose of a company is to generate profits. Companies must be able to generate profits for a certain period in order to maintain long-term survival. High and low ROA in Islamic banking can be influenced by the existence of business risks and Good Corporate Governance (GCG). This study was conducted to determine the role of good corporate governance in reducing the impact of financing risk on the profitability of Islamic banking. The population used in this study is Islamic commercial banks that implement good corporate governance. The sample selection technique used is purposive sampling. Samples that fit the criteria were obtained by 12 Islamic banks during the 2012-2017 observation period. The analytical tool used in this study is OLS regression and hypothesis testing using t test, f test, and determination coefficient using SPSS Statistics 22 and Microsoft Excel 2013 applications. The results of this study indicate that the financing risk variable has a negative effect on profitability. GCG variables have a positive effect on profitability and GCG variables can reduce the negative impact of financing risk on profitability.